High-precision attitude determination using spaceborne gravity gradiometer and gyroscope. (November 2022) - Sun, Xiucong; Mao, Xuejian; Chen, Pei
Abstract: This study investigates the application of a spaceborne gravity gradiometer to spacecraft attitude determination. Considering that the gradiometer raw measurements are influenced by angular rotation, a gyroscope is integrated to provide angular velocity information. To deal with unknown biases in both gradiometer and gyroscope measurements, a multiplicative extended Kalman filter (MEKF) is developed to estimate the attitude states and the instrument biases simultaneously. In addition, the cross-correlation between gyroscope measurements and gyroscope-compensated gradiometer measurements is analyzed. The MEKF algorithm is modified accordingly to cope with the correlation problem. Simulation scenarios with two different attitude modes are built to test the algorithm. With a gradiometer of 0.1 E (1 E = 10 −9 s −2 ) accuracy and a navigation-grade gyroscope, attitude determination accuracy of several arcsecs is obtained. Real data from the GOCE (gravity field and steady-state ocean circulation explorer) spacecraft are also used to test the algorithm. Yaw, pitch, and roll angle errors of 2.8 arcsec, 20.9 arcsec, and 11.3 arcsec are achieved, respectively. The method can directly estimate a spacecraft's attitude relative to the Earth-centered Earth-fixed (ECEF) frame and is promising for high-precision spacecraft attitude determination in Earth-oriented missions. Highlights: The spaceborne gravity gradiometer is used for spacecraft attitude determination. The attitude states and instrument biases are simultaneously estimated. The correlation between the process and measurement noises is analyzed. High-precision attitude determination relative to the ECEF frame is realized.